The performance of Permodalan Nasional Berhad (PNB): based on the profitability analysis / Intan Maizura Abdul Rashid - Abdul Rashid, Intan Maizura (Faculty of Business and Management, 2010)
The purpose of this study is to evaluate the financial performance of Permodalan Nasional Berhad (PNB) in term of profitability, to recognize the gap between theory and practice of company profitability management and to provide suggestions to improve the company profitability. A secondary data was used to evaluate the profitability ratios included in PNB annual reports from year 2001 until 2005. Profitability ratios consist of net profit margin, gross profit margin, operating profit margin, return on asset and return on equity. The results reveal that profitability performance of Permodalan Nasional Berhad (PNB) is not efficient due to low on sales and high on cost for the years 2001 to 2005. For better performance in future, PNB need to focus merely on operational efficiency and operational effectiveness which might directly influence the survival of a company (Chien and Song, 2004).